Troubleshooting, optimization and robustness testing of CeBER process for c-phycocyanin extraction and purification from spirulina - Kadir, Uzair (Department of Chemical Engineering, 2025)
c-Phycocyanin is a natural pigment, found as an intracellular protein in various microalgae. One of the most common sources of c-phycocyanin is Arthrospira platensis, more commonly known as Spirulina. Spirulina is a cyanobacterium, widely renowned for its many health benefits which, experts say, are a direct result of c-phycocyanin (Vernes, et al., 2015). Previous researchers in CeBER have demonstrated and patented a process to produce cosmetic grade c-phycocyanin (> 1.5 purity ratio) from Spirulina. The focus of this study was to optimize operating conditions for the key unit procedures posed previously for the CeBER patented process. The experimental work was performed in two main steps. The first considered the individual unit procedures (cell disruption via bead-milling, c-phycocyanin leaching rom biomass, cell debris removal via centrifugation, c-phycocyanin purification via polyethylene glycol-citrate and polyethylene glycol-maltodextrin aqueous two-phase separation, c-phycocyanin purification via ammonium sulfate precipitation), where the main aim was to optimize the operating conditions of the units and to mitigate redundancies in the pool of unit procedures. The second step involved assessing the performance of the overall process operating at the newly found operating conditions. Robustness of the process was qualified through the use of three different dried Spirulina powder samples (sourced from different suppliers) for the experiments. Bead-milling was demonstrated to narrow out the particle size distributions as expected, however a shift towards smaller cut sizes was only observed for the larger dried powders tested. In subsequent leaching, bead-milling did increase the initial extraction rate of c-phycocyanin from dried Spirulina powder. However, it was found that bead-milling may have no effect in the overall leaching time taken to reach an equilibrium concentration of c-phycocyanin in the crude extract. Bead-milling was also shown to have either little to no benefit in the recovery of product containing supernatant over the cell debris removal step. It was found that the c-phycocyanin leaching kinetics from the dried Spirulina powders could not be reliably predicting using standard models in literature. The highest R2 obtained was 0.95 for the fit of a 2nd order kinetic model to a Carbocraft milled sample. Most other samples tested did not yield a good correlation to first or second order leaching kinetics. It was found that to reach an equilibrium concentration across all samples, the minimum leaching time required was 19 hours. The crude extract purity ratios achieved were approximately 0.46, 0.41 and 0.12 in the Brenntag, Carbocraft and Indian Spirulina powder samples' crude extracts, respectively. As predicted, an increase in the g force used for cell debris removal via centrifugation yielded an increase in recovery of the product-containing supernatant. The highest recoveries were achieved at 10 000 g of operation. It was shown that a two-stage cell debris removal with an inter-stage rinsing step improved c-phycocyanin recovery overall. It was found that both of the ATPS systems investigated by previous CeBER researchers did not perform sufficiently robustly when required to handle a variation in the Spirulina source and hence crude extract feed. As such, the ATPS steps was deemed unsuitable for use in a commercialisation process and were removed from the process testing scope. Owing to the removal of the ATPS steps, microfiltration (0.22 m aperture) was added to the end of the process as an additional c-phycocyanin purification step. The ammonium sulfate precipitation train was optimized by identifying the ammonium sulfate concentrations that trigger selective c-phycocyanin precipitation and tracking how purity changes over concentration changes too. It was shown that a two-stage ammonium sulfate precipitation will yield a purer c-phycocyanin product than a single stage, producing a product stream with a higher final purity ratio and with less cell debris content. The ammonium sulfate saturation fraction recommended for the first stage is 0.22 where the supernatant is sequestered and treated with additional ammonium sulfate to achieve 0.45 saturation for the second stage. The c-phycocyanin is precipitated out in the second stage. The full runs of the process at the newly established “best” operating conditions yielded maximum purity ratios of 0.90 ± 0.02, 0.79 ± 0.03, 0.46 ± 0.03 for the Brenntag, Carbocraft and Indian dried Spirulina powders respectively. Thus, cosmetic grade c-phycocyanin was not achieved by any of the samples and food grade (> 0.7) only achieved using the Brenntag and Carbocraft samples. The recoveries were 24 ± 8%, 66 ± 8% and 65 ± 14% for the Brenntag, Carbocraft and Indian samples, respectively. It appears that, despite the low recovery obtained in the runs using the Brenntag powder, the amended process is robust enough to extract and purify c-phycocyanin from Spirulina, albeit without achieving the overall aim of cosmetic grade. The overall purification factors from the crude extract were approximately 2.6, 2.2 and 4.4 for the Brenntag, Carbocraft and Indian samples, respectively. These purification factors are not far off from those reported in literature for c-phycocyanin purification processes. It is, therefore, recommended that the process put more emphasis on increasing the purity ratio in the crude extract through means of using fresh Spirulina and chitosan/activated-charcoal adsorption techniques (as recommended by Hockey (2020) and Payne (2023)). With these changes it is probable that the amended process will achieve cosmetic grade purity. Further work should also be performed on increasing the recovery, especially over the precipitation stages, without compromising purity.